1999
DOI: 10.4278/0890-1171-13.4.215
|View full text |Cite
|
Sign up to set email alerts
|

Incentives and Barriers to Physical Activity for Working Women

Abstract: A questionnaire was completed by 393 working women to examine incentives and barriers to physical activity based on the stages of change from the transtheoretical model. Using Chi Square tests, differences were found across the five stages suggesting that work site programs be designed and tailored for women at different stages of readiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 5 publications
7
42
2
Order By: Relevance
“…Similar to other reports [21] [22] [23], female LTPA participation was found to be lower than their male counterparts. A hypothesis given to explain this gender difference in LTPA behavior is that boys, from their very young age, are socialized into sport roles more than girls [24] [25].…”
Section: Ltpa Statussupporting
confidence: 79%
“…Similar to other reports [21] [22] [23], female LTPA participation was found to be lower than their male counterparts. A hypothesis given to explain this gender difference in LTPA behavior is that boys, from their very young age, are socialized into sport roles more than girls [24] [25].…”
Section: Ltpa Statussupporting
confidence: 79%
“…For populations like young and midlife women who have been shown to have some of the lowest levels of exercise participation in the community (Armstrong et al, 2000), less experience with exercise may perpetrate the problem of inactivity because women may perceive more barriers to exercise than are necessary. Descriptive studies certainly show that women in this age group perceive many barriers to engaging in exercise (Anderson, 2003;Brown, Brown, Miller, & Hanson, 2001;Jaffee, Lutter, Rex, Hawkes, & Bucaccio, 1999;Johnson, Corrigan, Dubbert, & Gramling, 1990). Interventions that simply allow women to build up their exercise experience can, thus, be expected to assist in influencing their future exercise behaviour, both directly, and through creating more realistic perceptions of control.…”
Section: Enhancing the Prediction Of Behaviourmentioning
confidence: 99%
“…[3][4][5][6] Previous work has shown that women living in rural areas cite environmental characteristics as barriers. 10 Our findings suggest that rural mothers also attribute internal forces to their barriers to participation in physical activity.…”
mentioning
confidence: 99%
“…1 In spite of public health efforts to promote physical activity, as many as one in four women do not engage in any physical activity. 2 Women's most commonly perceived barriers to physical activity are lack of time, [3][4][5][6] lack of support, 7 and lack of willpower. 7 One study suggested that mothers are at even higher risk for not getting enough activity than women without children because they have more barriers.…”
mentioning
confidence: 99%